INTERNATIONAL FORUM “OLD AND NEW MEDIA: ALONG THE PATH TOWARDS A NEW AESTHETICS” / МЕЖДУНАРОДНЫЙ ФОРУМ «СТАРЫЕ И НОВЫЕ МЕДИА: ПУТИ К НОВОЙ ЭСТЕТИКЕ» - BOGATYRYOVA ELENA A. (Наука телевидения, 2019)
The article analyzes the results of the International Forum “Starye i novye media: put k novoy estetike:” [“Old and New Forms of Media: Paths Towards New Aesthetics”], which took place in Moscow on March 26–29, 2019. The organizers of this scholarly event were: the Federal State Budget Scholarly-Research Institution “the State Institute for Art Studies” and the Autonomous Non-Commercial Organization for Higher Education “Institute for Cinema and Television (GITR).” The conference brought together researches of the arts of the screen of all types and genres — from the cinematograph of the Lumieres to internet-serial movies and internet art. Over 80 scholars from scholarly research and educational institutions of Russia and other countries took part in the forum. As the conference has shown, the contemporary stage of research of media differs from the media research of the second half of the 20th century, as well as the research of the turn of the 1990s and the 200s. first of all, new forms of media are already not regarded as “outward expansions of the human being.” Second, assertions and apprehensions regarding the hitherto unknown consequences of the interactions of people with computer technologies have been replaced by detailed descriptions of such consequences. The opportunity has appeared to generalize the experience of the research of media in the 1990s and to come up with conclusions regarding certain calculations uttered during that time. The issues examined within the framework of the conference included philosophical and methodological questions regarding research of media, questions of the aesthetical significance of digital art, influences of new media on the visual arts, issues of transformations of aesthetical perception, relevant questions of contemporary mass media, questions of the ethics of scholarly publications, etc. The conference demonstrated the need for new methods of research which would be relevant for new media, the need for development of new aesthetic approaches, the expansion of the categorical apparatus of aesthetics capable of spanning the new media reality and phenomena of digital art. Along with the formulation of the enumerated questions, the presentations of the participants of the conference concretized the conclusions about the influence of new media on the cognitive capabilities of man, his means of action, “new plasticity” and a new way of living. Notice was made of alarming tendencies of transforming consciousness into that of “gamers,” reacting in correlations with certain algorithms, and a transference from discourse and substantiations towards reactions and evaluations. The conception of “digital art” turned out to be heterogeneous and included in itself of diverse types and genres. В статье анализируются итоги Международного форума «Старые и новые медиа: пути к новой эстетике», который состоялся в Москве с 26 по 29 марта 2019 г. Организаторы научного мероприятия — Федеральное государственное бюджетное научно-исследовательское учреждение «Государственный институт искусствознания» и Автономная некоммерческая организация высшего образования «Институт кино и телевидения (ГИТР)». Конференция объединила исследователей экранных искусств всех видов и жанров — от кинематографа Люмьеров до Интернет-сериалов и сетевого искусства. В форуме принимали участие более 80 ученых из российских и зарубежных научно-исследовательских и учебных институтов. Как показала конференция, современный этап исследования медиа отличается от медиаисследований второй половины ХХ в., а также исследований рубежа 1990–2000 гг. Во-первых, новые медиа уже не рассматриваются только как «внешние расширения человека». Во-вторых, констатации и опасения по поводу неизвестных пока последствий взаимодействия человека с компьютерными технологиями сменились подробными описаниями этих последствий. Появилась возможность обобщить опыт исследований медиа в 1990-е гг. и сделать выводы относительно некоторых высказанных в то время прогнозов. В рамках конференции были рассмотрены философские и методологические вопросы медиаисследований, вопросы эстетической значимости цифрового искусства, влияния новых медиа на изобразительное искусство, проблемы трансформации эстетического восприятия, актуальные вопросы современных масс-медиа, вопросы этики научных публикаций и др. Конференция продемонстрировала потребность в новых методах исследования, которые были бы релевантны новым медиа, необходимость разработки новых эстетических подходов, расширения категориального аппарата эстетики, способного охватить новую медиареальность и явления цифрового искусства. Наряду с формулировкой перечисленных вопросов, в докладах участников конференции были конкретизированы выводы о влиянии новых медиа на познавательные способности человека, его способ действия, «новую пластику», образ жизни. Отмечались настораживающие тенденции к превращению сознания в «геймерское», реагирующее в соответствии с определенным алгоритмом, переход от рассуждений и обоснований к реакциям и оценкам. Понятие «цифровое искусство» оказалось неоднородным, включающим в себя различные виды жанры.